Public Ocular Health problems and guidelines for their solution - Miranda-Vargas Fano, Mauricio (2019)
It is important and crucial to begin in a committed way to face the different ocular diseases chronologically framed according to statistical, epidemiological and demographic studies in each region of the country to improve the level of attention of the population.This would lead to the formation of multidisciplinary teams that work inter-sectorally to combat the prevailing pathologies of eye problems: in neonates such as Retinopathy of Prematurity (ROP), Retinoblastoma, visual defects and amblyopia of childhood and adolescence; infectious and degenerative conditions of the ocular surface such as pterygium, an important cause of blindness, various types of conjunctivitis and corneal ulcers that compromise vision; and in the elderly, glaucoma, cataract and retinal, macular and vitreous problems associated with systemic, metabolic and degenerative diseases.